Classroom assignments as measures of teaching quality. (April 2018) - Joyce, Jeanette; Gitomer, Drew H.; Iaconangelo, Charles J.
Abstract: We investigate classroom assignments and resulting student work to identify important characteristics of assignments in terms of instructional quality and their validity as measures of teaching quality. We examine assignment quality within a large-scale project exploring multiple measures including classroom observations, teacher knowledge measures, and value-added estimates based on student achievement scores. Analyses included descriptive statistics, multivariate analyses to understand factors contributing to score variance, and correlational analyses exploring the relationship of assignment scores to other measures. Results indicate relatively low demand levels in all teacher assignments, a marked difference in score distributions for mathematics (math) and English language arts (ELA), and a substantial relationship between what was asked of and produced by students. Relationships between assignments scores, classroom characteristics, and other measures of teaching quality are examined for both domains. These findings help us understand the nature of and factors associated with assignment quality in terms of intellectual demand. Highlights: Intellectual demand of assignments for math and English language arts is limited. Intellectual quality of student work is systematically related to assignment demand. Assignment quality is related to classroom demographics and academic achievement. Assignments complement classroom observations as a measure of classroom interaction.